2022
DOI: 10.21203/rs.3.rs-523385/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Rural Women’s Nutrition Security Status in Northwest Ethiopia

Abstract: Background: Nutrition security of women is one of the most vital foundations for overall development and wellbeing of society. Since understanding the factors that influence the nutrition security of women is very important for implementing appropriate interventions, this study was conducted to determine the determinants of the nutrition security status of rural women in Northwest Ethiopia. Methods: Survey data were collected from 197 rural women randomly selected using a two-stage sampling method (Cluster sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
1
Order By: Relevance
“…These are the people with better economic status in the kebele. The weight, the height, and the BMI of nutritionally insecure women are 44 kg, 1.45 m, and 15.8 kg/m2 (Teshome et al, 2022). This showed that the body mass index of the previous study is higher than the current result.…”
Section: The State Of Nutrition In the Districtcontrasting
confidence: 57%
“…These are the people with better economic status in the kebele. The weight, the height, and the BMI of nutritionally insecure women are 44 kg, 1.45 m, and 15.8 kg/m2 (Teshome et al, 2022). This showed that the body mass index of the previous study is higher than the current result.…”
Section: The State Of Nutrition In the Districtcontrasting
confidence: 57%